2013
DOI: 10.1002/lt.23634
|View full text |Cite
|
Sign up to set email alerts
|

Predicting early allograft failure and mortality after liver transplantation: The role of the postoperative model for end-stage liver disease score

Abstract: Early allograft dysfunction (EAD) is a serious complication after liver transplantation (LT).There is no uniform definition of EAD, and most definitions are based on arbitrary laboratory values. The aim of this study was to devise a definition of EAD that maximizes the predictive power for early death and graft failure. In this single-center, retrospective study, the ability of the international normalized ratio (INR), total bilirubin, aspartate aminotransferase (AST), physiological Model for End-Stage Liver D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 22 publications
3
52
1
2
Order By: Relevance
“…1 A previous publication from a single institution reported an incidence of 39.8%, but the breakdown of DCD and DBD allografts was not reported. 21 The University of Western Ontario reported a series of 38 recipients of DCD allografts, among whom 26 (68%) met the criteria for EAD. 13 In its comparative cohort of DBD recipients, only 19 of 89 (21%) met the criteria for EAD.…”
Section: Discussionmentioning
confidence: 99%
“…1 A previous publication from a single institution reported an incidence of 39.8%, but the breakdown of DCD and DBD allografts was not reported. 21 The University of Western Ontario reported a series of 38 recipients of DCD allografts, among whom 26 (68%) met the criteria for EAD. 13 In its comparative cohort of DBD recipients, only 19 of 89 (21%) met the criteria for EAD.…”
Section: Discussionmentioning
confidence: 99%
“…The value of the MELD score in predicting EAD within the first week, or mortality within 90 days post-transplant, was emphasized by Wagener et al (20) A study involving 66 transplanted patients (21) suggested peak serum AST investigation should be performed within the 5-11-hour post-reperfusion time window, given AST levels are known to drop by half within the first postoperative day. (21) This finding is highly significant, bearing in mind the lack of a consensus among organ transplant centers as to the best time point for the first serum AST level determination.…”
Section: Early Allograft Dysfunctionmentioning
confidence: 99%
“…Early post-transplant prognostic scores are of greater value, and several has previously been evaluated (12,13,(15)(16)(17). The most easily applicable score with a good predictive value is the post-transplant MELD score.…”
Section: /24mentioning
confidence: 99%
“…The pre-transplant MELD score predicts death on the waiting list, but poorly predicts outcome after liver transplantation (6)(7)(8)(9)(10)(11). In contrast, the MELD score measured early after liver transplantation, has been found to be a reasonable predictor of 3-month mortality and maybe superior to other prognostic scores, although it remains unknown whether the prognostic value of the MELD score persists if the association is adjusted for known risk-factors of a poor outcome (12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%